Non‐ionic Dendronized Multiamphiphilic Polymers as Nanocarriers for Biomedical Applications. Issue 6 (6th December 2012) - Gupta, Shilpi; Schade, Boris; Kumar, Sumit; Böttcher, Christoph; Sharma, Sunil K.; Haag, Rainer
Abstract A new class of non‐ionic dendronized multiamphiphilic polymers is prepared from a biodegradable (AB)n‐type diblock polymer synthesized from 2‐azido‐1, 3‐propanediol (azido glycerol) and polyethylene glycol (PEG)‐600 diethylester using Novozym‐435 (Candida antarctica lipase) as a biocatalyst, following a well‐established biocatalytic route. These polymers are functionalized with dendritic polyglycerols (G1 and G2) and octadecyl chains in different functionalization levels via click chemistry to generate dendronized multiamphiphilic polymers. Surface tension measurements and dynamic light scattering studies reveal that all of the multiamphiphilic polymers spontaneously self‐assemble in aqueous solution. Cryogenic transmission electron microscopy further proves the formation of multiamphiphiles towards monodisperse spherical micelles of about 7–9 nm in diameter. The evidence from UV–vis and fluorescence spectroscopy suggests the effective solubilization of hydrophobic guests like pyrene and 1‐anilinonaphthalene‐8‐sulfonic acid within the hydrophobic core of the micelles. These results demonstrate the potential of these dendronized multiamphiphilic polymers for the development of prospective drug delivery systems for the solubilization of poorly water soluble drugs.